Analisis Dan Perancangan Sistem Pencatatan Dan Pemantauan Kekeruhan Air Berbasis Website - Rivaldi, Ikvi Akmal; Utomo, Pradita Eko Prasetyo; A, Muhammad Razi (Prodi Sistem Informasi Universitas Dharma Andalas, 2026)
The utilization of web-based information systems has been widely adopted to facilitate easier user access to information. Specifically, PAM Tirta Tempino requires a system to manage customer meter recording data and monitor water turbidity quickly and accurately. Therefore, this study aims to design and develop a web-based Information System for Recording and Monitoring Water Turbidity that ensures accessibility for users anytime and anywhere. The system development utilizes the Rapid Application Development (RAD) method. The result of this research is a web-based information system architectural design modeled using Unified Modeling Language (UML), allowing users (Head, Officer, and Customer) to manage and view data according to their respective access rights. Furthermore, the design was verified using the Requirement Traceability Matrix (RTM), yielding valid results which demonstrate that the design fulfills all specified requirements.